(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2022)
This research has been prepared to show the extent to which the reflection of application of the international Accounting Standard No. (IAS 21) has been adopted by the economic units in the Republic of Iraq and its impact resulting from changes in foreign exchange rates on the tax outcome for the benefit of the General Tax Authority. The financial statements of a group of banks operating in the private sector were dealt with as a sample for research to find out the amount of amounts realized from the application of the relevant standard, The researcher relied on the method of financial analysis of these data, which was obtained from the website of the Securities Commission and conducting personal interviews for a number of university professors, chartered accountants, financial experts, employees of the Central Bank of Iraq , banks and the General Tax Authority to benefit from their opinions and information that enriched the research